Pengembangan Metode Discovery Learning Dengan Memanfaatkan Media Pembelajaran Matematika Untuk Menghindari Mind In Chaos Siswa Dalam Pembelajaran Matematika - Ramadina, Ina; Dwiarifiyanti, Septian; Sahrudin, Asep; Firmansyah, Eka (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2019)
: This study aims to find out (1) whether or not there is an increase in mathematical creative thinking skills of Madrasah Aliyah students; (2) Student activities during mathematics learning with the connected mathematics project Learning model. The research method used is the quasi-experimental method. The population in the study was class XI Madrasah Aliyah Mathla'ul Anwar Pusat Menes Pandeglang District, while the sample was taken randomly from two classes of six classes in the school. Class XI Religion is an experimental class, namely the class that has learned to apply the connected mathematics project and class XI IPS as a control class, namely the class whose learning applies conventional learning. Question test data were analyzed by descriptive and inferential statistics using the average difference test. The results of the study show: (1) There is an increase in mathematical creative thinking skills using the connected mathematics project learning model; (2) Positive student activities during mathematics learning with the connected mathematics project learning model.